Facile Fabrication of Well‐Dispersed Pt Nanoparticles in Mesoporous Silica with Large Open Spaces and Their Catalytic Applications. Issue 27 (1st June 2016) - Liu, Xianchun; Chen, Dashu; Chen, Lin; Jin, Renxi; Xing, Shuangxi; Xing, Hongzhu; Xing, Yan; Su, Zhongmin
Abstract: In this paper, a facile strategy is reported for the preparation of well‐dispersed Pt nanoparticles in ordered mesoporous silica (Pt@OMS) by using a hybrid mesoporous phenolic resin‐silica nanocomposite as the parent material. The phenolic resin polymer is proposed herein to be the key in preventing the aggregation of Pt nanoparticles during their formation process and making contributions both to enhance the surface area and enlarge the pore size of the support. The Pt@OMS proves to be a highly active and stable catalyst for both gas‐phase oxidation of CO and liquid‐phase hydrogenation of 4‐nitrophenol. This work might open new avenues for the preparation of noble metal nanoparticles in mesoporous silica with unique structures for catalytic applications. Abstract : Supported catalysts : Well‐dispersed Pt nanoparticles assembled in ordered mesoporous silica with an unique structure were synthesized and exhibited excellent catalytic performance with remarkable stability in both gas‐ and liquid‐phase reactions (see figure).